2018
DOI: 10.15252/embj.201798664
|View full text |Cite
|
Sign up to set email alerts
|

The Helicobacter pylori adhesin protein HopQ exploits the dimer interface of human CEACAMs to facilitate translocation of the oncoprotein CagA

Abstract: infects half of the world's population, and strains that encode the type IV secretion system for injection of the oncoprotein CagA into host gastric epithelial cells are associated with elevated levels of cancer. CagA translocation into host cells is dependent on interactions between the adhesin protein HopQ and human CEACAMs. Here, we present high-resolution structures of several HopQ-CEACAM complexes and CEACAMs in their monomeric and dimeric forms establishing that HopQ uses a coupled folding and binding me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 61 publications
9
84
1
Order By: Relevance
“…5B,C). Although it has been suggested that HopQ affects the adherence to human cells (Bonsor et al, 2018), we observed no difference in the adhesion to AGS cells with any of the strains (Fig. 5E).…”
Section: Hopq Type Ib and Hopq Type II Are Required For Nf-κb Activationcontrasting
confidence: 69%
“…5B,C). Although it has been suggested that HopQ affects the adherence to human cells (Bonsor et al, 2018), we observed no difference in the adhesion to AGS cells with any of the strains (Fig. 5E).…”
Section: Hopq Type Ib and Hopq Type II Are Required For Nf-κb Activationcontrasting
confidence: 69%
“…Recently, the first high resolution structures (2.68-2.8 Å) of the hCEACAM1 IgV domain in complex with a bacterial receptor were solved with the H. pylori outer membrane adhesin HopQ (PDB ID 6AW2, 6GBG) [62,63]. Although HopQ adopts an alpha-beta folded structure that diverges significantly from Opa CEA , its mode of binding to the GFCC'C" surface on CEACAM1 is conserved with other microbial ligands.…”
Section: Ceacam1 Igv Heterophilic Interactions With Host Ligands-thementioning
confidence: 99%
“…Four loops (α3-β1, β2-α4, α5-α6, α7-α8) form a binding surface that allows for the β2-α4 loop to participate in an extensive van der Waals and hydrogen bonding network with the CEACAM1 IgV GFCC'C" surface. This specifically involves interactions with CEACAM1 residues on the CC' loop (F29, V39, Q44) and FG loop (Q89, I91, V96) [63]. HopQ binds to CEACAM1 through a distinct coupled folding and binding mechanism [63] that exhibits high affinity for CEACAM1 IgV with a binding constant that exceeds CEACAM1 homodimerization (K D =23-279 nM) [43,63].…”
Section: Ceacam1 Igv Heterophilic Interactions With Host Ligands-thementioning
confidence: 99%
See 1 more Smart Citation
“…Once this first contact is achieved, the T4SS can establish binding to numerous host cell surface factors such as integrin receptors and phosphatidylserine to assist the delivery of CagA, possibly in lipid rafts (cholesterol-rich microdomains) in the focal adhesions (Backert et al, 2015;Hayashi et al, 2012;Kwok et al, 2007;Lai et al, 2008;Posselt, Backert, & Wessler, 2013;Tegtmeyer, Wessler, et al, 2017). A fourth group of factors, the CEACAM receptors and their bacterial ligand HopQ, came into play just recently and are also required for full T4SS function (Bonsor et al, 2018;Javaheri et al, 2016;Koniger et al, 2016;Moonens et al, 2018). A fourth group of factors, the CEACAM receptors and their bacterial ligand HopQ, came into play just recently and are also required for full T4SS function (Bonsor et al, 2018;Javaheri et al, 2016;Koniger et al, 2016;Moonens et al, 2018).…”
Section: Expression Of Ceacam1 and Ceacam5 Enhances Caga-mediated Tmentioning
confidence: 99%